PENGARUH PENGGUNAAN MEDIA TORSO TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPA - Firda Halawati (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The purpose of this research are (1) to know the use of torso media on science subjects in SDN Cikahuripan, (2) to know the result of student learning on science subjects by using torso media in Public Elementary School Cikahuripan, and (3) to knoware there any influence by using torso media on science subject in Public Elementary School Cikahuripan. This research used Pre-experimental method with one group pretest posttest design. The population in this research are all students of Public Elementary School Cikahuripan which amounted to 364 students. In sampling technique used purposive sampling technique. The samples of this study was taken from two classes, those are VA class as a experiment class totally as many as 32 students and VB class as an control class totally 28 students, so all the samples that as many 60 students. Mastery of matter about the human digestive system is measured using multiple choice tests. The test is given on pretest and final test (posttest). Before the test is given, the test instrument has first been analyzed the validity, reliability, problem level and the differentiation of the problem. Analysis of hypothesis testing of data in this study using Independent Samples T-Test that had previously been tested normality and homogeneity. The results of this study indicates that (1) The use of torso media in science learning subjects of human digestive system in Public Elementary School Cikahuripan is good. (2) After the data result from prelimiary and final test were analyze, there is obtained the average pretest result in experimental class as 62.81 and posttest as 85.78, so from the average of pretest and posttest there is an increase of 37%. As well as the average pretest control class are about 60.18 and posttest about 79.64 so the average pretest and posttest increase is about 33%. Those are reinforced by the average difference test (t-test) which is obtained > is 3.031> 1672 and the significant point below 0.05 that is 0.04 <0.05. Based on N-Gain test, that has been obtained the value of N-Gain from experiment class as 0.71 as a high criteria and for control class with amount of 0.49 with medium criteria. (3) based on these results show that received and rejected. So it can be concluded that there has an influence in using torso media to student result study science subjects in Public Elementary School Cikahuripan.